Age and gender based biomechanical shape and size analysis of the pediatric brain - Danelson, Kerry A; Geer, Carol P; Stitzel, Joel D; Slice, Dennis E; Takhounts, Erik G (Stapp car crash journal, 2008)
Injuries caused by motor vehicle crashes (MVCs) are the leading cause of head injury and death for children in the United States. This study aims to describe the shape and size (morphologic) changes of the cerebrum, cerebellum, brainstem, and ventricles of the pediatric occupant to better predict injury and assess how these changes affect finite element model (FEM) response. To quantify morphologic differences in the brain, a Generalized Procrustes Analysis (GPA) with a sliding landmark method was conducted to isolate morphologic changes using magnetic resonance images of 63 normal subjects. This type of geometric morphometric analysis was selected for its ability to identify homologous landmarks on structures with few true landmarks and isolate the shape and size of the individuals studied. From the resulting landmark coordinates, the shape and size changes were regressed against age to develop a model describing morphologic changes in the pediatric brain as a function of age. The most statistically significant shape change was in the cerebrum with p-values of 0.00346 for males and 0.00829 for females. The age-based model explains over 80% of the variation in size in the cerebrum. Using size and shape models, affine transformations were applied to the SIMon FEM to determine differences in response given differences in size and size plus shape. The geometric centroid of the elements exceeding 15% strain was calculated and compared to the geometric centroid of the entire structure. Given the same Haversine pulse, the centroid location, a metric for the spatial distribution of the elements exceeding an injury threshold, varied based on which transformation was applied to the model. To assess the overall response of the model, three injury metrics were examined to determine the magnitude of the metrics each element sustained and the overall volume of elements that experienced that value. These results suggested that the overall response of the model was driven by the variation in size, with little variation due to changes in shape. This study demonstrates a new methodology to quantify the shape and size variation of the brain from infancy to adulthood. The use of the changes in shape and size when applied to a FEM suggests that there are differences in the spatial distribution of the elements that exceed a specific threshold based on shape but the overall volume of elements experiencing the specified magnitude was more dependent on the changes in the size of the model with little change due to shape.